Características clínicas y epidemiológicas relacionadas al síndrome coqueluchoide en pacientes menores de 5 años atendidos en el Hospital Apoyo Iquitos César Garayar García, durante los años 2019-2021 - Rubio Ocampo, Milagros del Rosario (2022)
The coqueluchoid syndrome is the set of signs and symptoms very difficult to differentiate from the clinical manifestations produced by pertussis, when the presence of Bordetella pertussis or parapertussis cannot be established, while other infectious or non-infectious causative agents are suspected. The coqueluchoid syndrome can occur in all age groups, with the most affected population being children, especially those under six months of age. In 2008, the World Health Organization estimated 89,000 deaths due to pertussis, and in 2017 reported 143,661 cases worldwide. In Peru, pertussis has a cyclical epidemiological behavior, with increases in cases every three to five years; however, the latest reports of cases reported in the last two decades show a decreasing trend of this disease. (3) In 2018, the national center for epidemiology, prevention and disease control reported that the departments of Loreto, Callao and La Libertad registered the highest incidence of reported cases nationwide. (10) Vaccination is the best strategy to prevent, reduce and control this disease, which should be a priority in high-risk areas to reduce the attrition rate and the accumulation of susceptible. (10) An observational, retrospective, and cross-sectional study was designed. The type of population sample will be non-probabilistic and will consist of hospitalized patients with clinical symptoms compatible with Coqueluchoid Syndrome; data collection will be by means of a data sheet and document review of medical records. The data collected will be processed in the SPSS program version 27.0, and the results obtained will be presented in simple frequency tables and percentages.